MAKNA TRADISI META’UA PADA MASYARAKAT BUTON DI KECAMATAN SIOMPU KABUPATEN BUTON SELATAN - Dewi Tasria; Amal; Erman Syarif (STKIP Subang, 2026)
This study aims to understand the process of the meta'ua tradition in the Buton community in Siompu District, to understand the meaning contained in the meta'ua tradition, and to understand the factors that influence the survival of the meta'ua tradition until today. This type of research is qualitative research with a phenomenological approach. In collecting data through observation, interviews, and documentation. The data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions. The results of this study are that the metau tradition began in ancient times and in its process began with pogaua, kaoluando wua, linda dance, humaano baruga, fomani dance, and aroano rewu. And the meanings contained in this tradition include the meaning of friendship and unity, spiritual meaning, the meaning of cultural preservation, religious meaning, and finally the meaning of caring for the environment. And the factors that influence so that this tradition continues to survive until now are the process of appointing parabela, the process of transferring wati, the process of changing traditional devices, and the community's increasing desire to maintain this culture even though it has shifted from the beginning and continues to follow the development of the times.